Blended synchronous learning : a handbook for educators. - Bower, Matt; Dalgarno, Barney; Kennedy, Gregor; Lee, Mark J. W.; Kenney, Jacqueline (Blended Synchronous Learning Project, 2014)
Handbook produced as a result of the Blended Synchronous Learning Project, that investigated how rich-media technologies could be used to unite remote and face-to-face students in the same live classes. Seven case studies of blended synchronous learning were conducted in higher education institutions around Australia. The handbook includes: a design framework for teachers wishing to implement blended synchronous lessons; a capabilities framework to support selection of suitable technologies; a literature review; case study reports; summary of study results; and a cross case analysis. [Executive summary, ed]